The Effectiveness of a Senior High School English Immersion Program on Graduates Communicative Competence and Academic Achievement in Higher Education - Damar Jati Pamungkas; Yeny Prastiwi; Agus Wijayanto; Nur Hidayat; Anam Sutopo (Universitas Muhammadiyah Surakarta, 2025)
The proliferation of English immersion programs in Indonesian secondary education necessitates empirical examination of their long-term effectiveness in preparing graduates for higher education demands. This qualitative phenomenological study investigates the sustained effects of senior high school English immersion programs on graduates' communicative competence and academic achievement in Indonesian university contexts. Through in-depth interviews with eight purposively selected program graduates (currently pursuing higher education across diverse disciplines and institutions), this research examines lived experiences of transitioning from immersion secondary education to English-medium instruction in universities. Phenomenological analysis following Moustakas (1994) revealed five essential themes: immersive environment as linguistic foundation, multidimensional communicative competence development, strategic advantages in higher education transition, sustained academic performance benefits, and confidence development as English users. Findings demonstrate that well-designed immersion programs develop integrated communicative competence across grammatical, sociolinguistic, discourse, and strategic dimensions, which transfers effectively to higher education contexts and contributes to graduates' academic success, intercultural competence, and expanded career opportunities. The study contributes empirical evidence from Indonesian EFL contexts regarding sustained immersion outcomes, validates Canale's (1983) communicative competence framework in immersion settings, and provides evidence-based recommendations for secondary and higher education stakeholders. Implications address program design, equity concerns, and the integration of language learning with identity development in Indonesian educational contexts.